MODELING TSUNAMI RUNUP DUE TO THE ANDAMAN TSUNAMI ALONG BEACHES IN MALAYSIA - Teh Su Yean (Proceedings of ICMSA, 2006)
In an earlier paper, we modeled the propagation of waves across the deep oceans due to tsunami created from an earthquake that occurred around Banda Aceh, Indonesia on December 26, 2004 by means of an in-house tsunami propagation model TUNA-M2. Tsunami wave heights were simulated from the deep ocean up to offshore coasts at depths exceeding 50 m. In this paper, we develop an in-house model TUNA-RP, based upon the finite difference method, to guide the tsunami waves at these offshore locations onto the shallow coasts up to the beaches. The inputs for this model TUNA-RP are derived from the output of TUNA-M2 simulations, accounting for combinations of various source generation conditions reported. The synoptically simulated runup heights along certain beaches in Malaysia will be compared to the runup heights surveyed after the tsunami occurrence. Numerical stability and accuracy of the model will be briefly discussed in conjunction with other analytical and empirical formulations